SITUATIONAL LEADERSHIP ON ISLAMIC EDUCATION - Oskar Hutagaluh, Aslan, Purniadi Putra, Abdul Wahab Syakhrani Sri Mulyono (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2020)
Every human being should be a leader both for himself and his family. In reality, not all of human can become leader who are leading the people they lead. This swriting is going to describe the situational leaders who have a leadership style in accordance with the prevailing circumstances of the current rapid social change in the context of islamic education. To explain the situational leadership in islamic education, this paper reviewed various islamic literatures both national and internation cotext. Therefore, the findings of this resaerch were the leadership in islamic intitution is not able to adjust the situation with the current changes. Morever, the Islamic educational institution a leader leads will not be able to compete with the general and Islamic educational institutions that have modernized using the curriculum desired by the government and outside community